“Underwear Rule” in Improving Sexual Abuse Prevention Attitudes among Parents of Intellectual Disabilities Adolescent - Rizqi Nur Aini; Fransiska Imavike Fevriasanty; Heni Dwi Windarwati (Sawwa: Jurnal Studi Gender, 2023)
Sexual abuse remains a prevalent issue among disabled individuals, particularly adolescents with intellectual disabilities. Parental lack of knowledge and negative attitudes towards sexual abuse contribute to its occurrence. This study aims to investigate the impact of “Underwear Rule” training on the attitudes of parents of adolescents with intellectual disabilities towards sexual abuse prevention. Employing a pre-experimental method with a one-group pretest-posttest design, the research involved 72 parents. The Wilcoxon test was utilized for analysis. The findings reveal a positive influence of “Underwear Rule” training on parents’ attitudes, enhancing their motivation to prevent sexual abuse in adolescents with intellectual disabilities. Collaboration among healthcare workers, educators, and parents is recommended to implement and integrate “Underwear Rule” training into daily activities, effectively preventing sexual abuse in this vulnerable population.